Xylan Decomposition in Plant Cell Walls as an Inducer of Surfactin Synthesis by Bacillus subtilis - Ida Szmigiel; Dorota Kwiatkowska; Marcin Łukaszewicz; Anna Krasowska (Biomolecules, 2021)
Hemicellulose is the second most abundant plant heterogenous biopolymer. Among products obtained from a wide range of agro-residues, biosurfactants, e.g., surfactin (SU), are gaining increasing interest. Our previous studies have shown that a Bacillus subtilis strain can successfully produce a significant amount of SU using a rapeseed cake. This work aimed to investigate plant hemicellulose components as substrates promoting SU’s efficient production by B. subtilis 87Y. Analyses of SU production, enzymatic activity and cell wall composition of hulled oat caryopses suggest that the main ingredients of plant hemicellulose, in particular xylan and its derivatives, may be responsible for an increased biosurfactant yield.